The Eloquence of the Holy Quran : Reading in “ Risalat AlNukat Fi Al-Quran “ As Perceived by Al-Rummany (384 of the Hegira) - محمد ماجد الدخيل; عبير عبيد الشبيل (Ar-Raniry: International Journal of Islamic Studies, 2015)
This study aims at examining the Eloquence of the Holy Quran as Perceived by Al-Rummany (384 of the Hegira) at the effect of some scholars, in regard to its ways sections, chapters, types and instances saw some modern scholars because the researcher really believes in the connection of Arab thetoric and its sciences with old Arab Qurani studies peculiar to the topic of the wondrous nature of the holy Quran. This study especially analyze Al-Rummany’s “Risalat Al-Nukat Fi Al-Quran “, in a detailed, descriptive way.